(untitled) (Eurasian Scientific Herald, 2025)
This article is dedicated to analyzing the role and significance of the concept of reflection in the educational process. The article examines reflection as one of the main components of the educational system, contributing to the enhancement of teachers’ professional skills, stimulating students’ self-development, and improving the effectiveness of the educational process. The text emphasizes the importance of reflection for analyzing pedagogical activities, evaluating the teacher’s own work, and exchanging opinions with students. The article also discusses the significance of the educational environment and the interaction between the teacher and the student, as well as the need for continuous improvement of teaching methods through reflection. It further explores how reflection can be applied in practice and how it influences the educational process, offering new approaches for educators